Enhanced Growth Potential of Cultured Rahbit Tracheal Epithelial Cells Following Exposure to N‐Methyl‐N′‐nitro‐N‐nitrosoguanidine - Kitamura, Hitoshi (Jpn J Cancer Res, 1993)
To establish a standardized model for the transformation of rabbit airway epithelial cells, we attempted to transform rabbit tracheal epithelial (RbTE) cells in culture with N‐methyl‐N′‐nitro‐N‐nitrosoguanidine (MNNG). RbTE cells, harvested by enzymatic digestion from male New Zealand white rabbits, were plated onto feeder layers of irradiated 3T3 cells. Control cells proliferated exponentially during the 2nd week of culture and reached the plateau phase by the 3rd week. Cells exposed to MNNG (0.1 γg/ml) proliferated in a fashion similar to the control cells, except that there was some delay before proliferation began. The clonogenic activity of RbTE cells rapidly decreased in parallel with the increase in cell population equally in the control and MNNG groups. During the late plateau phase, cells exposed to MNNG regained clonogenic activity, and this compartment size expanded with time, whereas the clonogenic activity in control cultures remained below the detectable level. In RbTE cell cultures exposed three times to 0.1 γg/ml MNNG, large, persistent and proliferating colonies emerged at a frequency of 1–3 × 10 x(−2) among the surviving clones, whereas all the control cultures eventually became senescent. The MNNG‐indnced alteration in the growth potential of RbTE cells, i.e., the extended lifespan, and the maintenance and even expansion of clonogenic activity, was similar to that of transformed rat tracheal epithelial cells. However, no immortal cell line could be established from these growth‐altered RbTE cells. We therefore concluded that the growth‐altered RbTE cells were partially transformed.